Identification of the Direct Effect of Self-Differentiation on Marital Satisfaction in Married Women - Kordbacheh, Soraya; Dokaneifard , Farideh; Nicknam , Mojgan (Psychology of Woman Journal, 2025)
Objective: The objective of this study was to identify the direct effect of self-differentiation on marital satisfaction in married women. Methods and Materials: This quantitative, applied research utilized a descriptive-correlational design with a structural modeling approach. The statistical population included all married women who visited counseling centers at the University of Tehran between February 2023 and August 2023. A sample of 330 participants was selected using convenience sampling. Data were collected using the ENRICH Marital Satisfaction Scale (1989) and the Self-Differentiation Scale developed by Skowron and Smith (2003). The data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (structural equation modeling). Findings: The results showed that the proposed structural model for marital satisfaction demonstrated an acceptable fit. Self-differentiation had a direct and significant effect on marital satisfaction among married women (P < .01). Conclusion: The findings suggest that self-differentiation plays a significant role in influencing marital satisfaction among married women, emphasizing the importance of self-differentiation in marital relationships.